O protagonismo infantil e suas interfaces com a realidade santarena - Sousa, Wanildo Figueiredo de (2010)
The history of childhood in Santarém includes several contexts, from the celebrities existence, which build our people s history, to résumé of writings of authors who were and are dedicated in defense of child s rights. Philippe Ariès glance, on his work Social history of child and family, has brought us near to medieval and modern reports on childish population, to many ways of being a child , to the disrespect and prejudice that surround children. Maria Luiza Marcílio, on her work History of children in Brazil, presents us the causes of children s abandonment in 19th century, among them, the subject of poverty, death or parents disregard, diseases, defense of noble women s honor, elitized, the family honor. In the 20th century, factors as urbanization, emigrations from rural area to urban area, the European immigration and woman s exemption on job market were and have been one of many causes of children s abandonment. Mary Del Priori s reports, on her work History of the children in Brazil, have been served as support to understand the childish illustration in the periods of Brazil Cologne, Empire and Republic. The educational emotional and ethical contempt to this group is perceptible since the first foundations of our politics; only the dominant group has enjoyed privilege because of an exclusionist and excluding philosophy. In the past, the famous Saint Houses of Mercy, the Wheels of the Exposed Ones were remarkable. Today the nomenclature has been changed for child s pastorals, day cares, shelters, homes, NGOs for children. The obtained reports at the records of the institutions that militate for child s rights have served us as base for historical verification before, during and after their implantation. The child of Santarém had not its rights warranted because of the lack of knowledge and political actions that could warrant or protect it. The political group, which should foment projects, didn t take an attitude, until the civil society was organized and has began the first fomentations on behalf of child s rights, starting the Council of Rights, Fund and Guardian Council. Now, countless institutions, especially the civil and religious society, have articulated and registered their projects in partnership with Municipal Council of Child's and Teenager s Rights, an agency of great importance on the development of public politics in defense of the tiny children s interests.